Investigation of aflatoxin production in three different Aspergillus species - Tóth-Buella, Barbara; Horváth, Levente; Kredics, László; Vágvölgyi, Csaba; Papp, Tamás; Bartók, Tibor; Varga, Mónika; Szekeres, András (Acta Biologica Szegediensis, 2025)
Mycotoxins are secondary metabolites produced by molds, particularly by Aspergillus species, with their production influenced by various environmental and other factors. The growth and physiology of fungi are affected by factors such as temperature, water activity, and time. The aim of this study was to identify the best aflatoxin-producing Aspergillus strain among known mycotoxigenic species and isolates and to fine-tune specific cultivation conditions to achieve the highest aflatoxin yield. For this purpose, aflatoxin production was tested in isolates belonging to Aspergillus pseudotamarii (1), A. minisclerotigenes (1), and A. parasiticus (3). The presence and quantity of aflatoxins were determined by HPLC with fluorescence detection. Among the examined strains, A. parasiticus SZMC 22361 proved to be the most suitable toxin-producing strain. Our findings suggest that the optimal conditions for aflatoxin production by this isolate on a maize substrate involve a water-to-substrate ratio of 1:1 (m/m) over a production period of approximately one week.